Spirometric Assessment of Lung Function in Garment Workers in Bangladesh: A Cross Sectional Study (Chest & Heart Journal, 2021)
Background: Exports of textiles and garments are the principal source of foreign exchange earnings in Bangladesh. Exports of textiles, clothing, and ready-made garments (RMG) account for 85% of Bangladesh’s total merchandise exports and provide employment to around 5 million workers. Workers of garment factories are susceptible to various respiratory morbid conditions, by virtue of workplace and working conditions and are at risk of suffering from various chronic respiratory illnesses. Early studies in textile workers throughout the world have focused on the relationship between hemp or cotton dust exposure and the development of a syndrome termed Byssinosis. Even though quite a few studies have been conducted in among garment workers in Bangladesh enough emphasis has not been given on the epidemiological aspects of chronic respiratory illnesses affecting pulmonary functions among the workers in these mills.Objective: The purpose of the study is to observe pulmonary function among garment workers in Bangladesh and compare it with unexposed population.Methods: This cross-sectional observational study was conducted at cotton mill in Gazipur, Dhaka, Bangladesh. A control group was taken from BSMMU for the purpose of comparison. A modified questionnaire was used to inquire about socio demographic characteristics, socioeconomic history, complete occupational history, potential confounding factors, physical parameters and spirometry was done among workers.Results: There was significant association of pulmonary function FEV1, FVC, PEF with cotton dust exposure and a significant reduction of both FEV1 predicted 2.92±0.38 and observed 2.47±0.67 p